Strategi Penegakan Hukum Penggelapan Pajak Korporasi melalui Offshore Finance dan Tax Haven - Muttaqien, Firman; Purwati, Ani (LPPM Institut Pendidikan Nusantara Global, 2025)
The utilization of offshore finance and tax haven jurisdictions by multinational corporations poses a serious threat to Indonesia’s fiscal sovereignty, as it facilitates cross-border tax evasion and illicit financial flows. This study examines the mechanisms underlying such practices and formulates law enforcement strategies aligned with international best practices. Using a normative juridical method with legislative and comparative approaches, the research integrates Corporate Criminal Liability Theory, John Rawls’ Theory of Justice, and Legal Effectiveness Theory as its analytical framework. The findings identify weaknesses in corporate criminal sanctions, low transparency of beneficial ownership, and suboptimal use of the Automatic Exchange of Information (AEoI). Recommendations include strengthening domestic regulations, enforcing corporate criminal liability, enhancing beneficial ownership disclosure, leveraging AI-based audit technology, and harmonizing with OECD BEPS and FATF recommendations. A comprehensive and adaptive law enforcement strategy is essential to curb cross-border tax evasion and uphold the principles of tax justice in Indonesia.